PENINGKATAN KUALITAS AUDIT : SUATU STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR INDONESIA - Asih Machfuzhoh (RISTANSI: Riset Akuntansi, 2020)
This study aims to determine the effect firm size, rotation audit, and audit fee for audit quality.The population in this study are manufactur companies listed on the Indonesia Stock Exchange during the period 2015-2018. Using the purposive sampling method, there were 31 companies complying criteria as samples. This study used secondary data from Indonesia Stock Exchange website. The results of this study indicate that: (1) Firm size has a significant positive effect on audit quality. (2) rotation audit a significant negative effect on audit quality. (3) audit fee has a significant positive effect on audit quality.